Rhamnaceae Juss. on the Flora of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
Information about the Rhamnaceae species in the flora of Ukraine is generalized. Keys for the determination of genera and species are created. Morphological descriptions and information about their distribution are given for each species nomenclature. Rhamnaceae species of natural flora of Ukraine is described in this paper. Four species are native (Frangula alnus Mill., Paliurus spina-christi Mill., Rhamnus cathartica L., R. tinctoria Waldst. et Kit.) and one species is alien (Rhamnus alaternus L.). We also provide information on species commonly cultivated in gardens and parks of Ukraine.
Keywords: Rhamnaceae, Flora of Ukraine.